1997
DOI: 10.1002/(sici)1097-4628(19971031)66:5<869::aid-app7>3.0.co;2-t
|View full text |Cite
|
Sign up to set email alerts
|

Radiation-induced grafting ofN,N?-dimethylaminoethylmethacrylate onto chitosan films

Abstract: Chitosan films were grafted with N,N-dimethylaminoethylmethacrylate using the 60 Co gamma irradiation method. The effect of solvent composition, monomer concentration, dose rate, and total dose on grafting was studied. The solvent composition has a marked effect on the degree of grafting. Maximum yield was obtained in the water-methanol (1 : 1) system. The percent grafting increased with monomer concentration and was found to be higher at a lower dose rate for a constant total dose of 0.216 Mrad. The tensile s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
35
0

Year Published

2001
2001
2013
2013

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(35 citation statements)
references
References 2 publications
0
35
0
Order By: Relevance
“…It was found that the grafting yield increased with the increase in the adsorbed dose. Singh and Roy have also reported radiation grafting of chitosan with N,N -dimethylaminoethylmethacrylate (DMAEMA) [39]. Parameters such as solvent composition, monomer concentration, radiation dose rate, and total dose/time were found to affect the rate of grafting and homopolymerization.…”
Section: Grafting Using Radiationmentioning
confidence: 99%
“…It was found that the grafting yield increased with the increase in the adsorbed dose. Singh and Roy have also reported radiation grafting of chitosan with N,N -dimethylaminoethylmethacrylate (DMAEMA) [39]. Parameters such as solvent composition, monomer concentration, radiation dose rate, and total dose/time were found to affect the rate of grafting and homopolymerization.…”
Section: Grafting Using Radiationmentioning
confidence: 99%
“…The study showed that permeation control can be achieved by varying the amount of cross-linking agent [181]. Hirano et al [182,183] prepared a series of membranes from chitosan and its derivatives, and the membranes showed improved dialysis properties. They observed that permeability properties of N-acetyl chitosan membranes were similar to those of an Amicon Diaflo membrane UM-10 (Amicon Ltd., England).…”
Section: Artificial Kidney Membranementioning
confidence: 99%
“…What's more, the adsorbents with different grafting yield (GY) can be easily prepared by controlling the irradiation conditions. Dimethylaminoethyl methacrylate (DMAEMA) has been grafted onto various matrix materials by radiation technique [20][21][22][23][24]. As tertiary and quaternary amino groups can be easily incorporated into matrix materials, the DMAEMA grafted materials have also been utilized for adsorption and separation of heavy metal ions [21,22,25].…”
Section: Introductionmentioning
confidence: 99%